2018
DOI: 10.1140/epjc/s10052-018-5654-y
|View full text |Cite
|
Sign up to set email alerts
|

Charged reflecting stars supporting charged massive scalar field configurations

Abstract: The recently published no-hair theorems of Hod, Bhattacharjee, and Sarkar have revealed the intriguing fact that horizonless compact reflecting stars cannot support spatially regular configurations made of scalar, vector and tensor fields. In the present paper we explicitly prove that the interesting no-hair behavior observed in these studies is not a generic feature of compact reflecting stars. In particular, we shall prove that charged reflecting stars can support charged massive scalar field configurations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 64 publications
5
32
0
Order By: Relevance
“…Similar phenomenological aspects regarding the interaction of massless bosonic fields with perfectly-reflecting Kerr-like ECOs have been reported in [25,26,54]. It was shown in particular that some ECOs or ECO analogues can only support static configurations of a scalar field for a discrete set of critical radii [54][55][56][57]. This also holds true for the present case, as shown in the Appendix B.…”
Section: A Numerical Methodssupporting
confidence: 85%
“…Similar phenomenological aspects regarding the interaction of massless bosonic fields with perfectly-reflecting Kerr-like ECOs have been reported in [25,26,54]. It was shown in particular that some ECOs or ECO analogues can only support static configurations of a scalar field for a discrete set of critical radii [54][55][56][57]. This also holds true for the present case, as shown in the Appendix B.…”
Section: A Numerical Methodssupporting
confidence: 85%
“…We should point out that this property is very different from cases in black holes, where black hole no hair theorem holds for any size of the horizon [35,36]. Similar to the charged shell case, it was found that large horizonless reflecting stars tend to have no scalar field hair [37][38][39][40][41][42]. Moreover, large horizonless stars with Neumann boundary conditions also cannot support the static scalar field hair [43,44].…”
Section: Introductionmentioning
confidence: 90%
“…In the charged background, reflecting shells can exclude scalar field hairs when the shell radius is large enough [43][44][45]. Large charged reflecting compact stars also cannot support the existence of scalar field hairs [46][47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%